2015
DOI: 10.46743/1082-7307/2015.1271
|View full text |Cite
|
Sign up to set email alerts
|

The Components of Dehumanization

Abstract: Dehumanization is a complex, relational and subjective phenomenon. Studies on it primarily focus on how it enables abuse in the midst of conflict, or how it shapes perceptions of others. Scholars, however, have not deconstructed it into components. The current article breaks down dehumanization into three components: elements, characteristics, and dimensions. It is hoped that the discussion of the connection between the three can encourage additional discussions on how each of the components contributes to deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The extensive occurrence of dehumanization in social relations affects interpersonal, institutional, and structural types of violence and peace (Barak, 2003). Studies have linked (de)humanization to language, emotion, ideology, behavior, laws, and institutions of society (Luna, 2015).…”
mentioning
confidence: 99%
“…The extensive occurrence of dehumanization in social relations affects interpersonal, institutional, and structural types of violence and peace (Barak, 2003). Studies have linked (de)humanization to language, emotion, ideology, behavior, laws, and institutions of society (Luna, 2015).…”
mentioning
confidence: 99%
“…The comparison revealed that their use encompassed several overlapping themes affecting various areas of life. "Areas of life" is a thematic category derived from the (Luna, 2015). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Additional Findingsmentioning
confidence: 99%
“…anecdotes reviewed that helped to visually reduce the data into tables (Luna, 2015). The associated themes covered perceptions of self or other; the physical and spatial experience of dehumanization; personal or others' behaviors; and limited conditions, rituals, or attitudes.…”
Section: Additional Findingsmentioning
confidence: 99%
See 2 more Smart Citations